Repeated video head impulse testing in patients is a stable measure of the passive vestibulo-ocular reflex - Mahfuz, M. Muntaseer; Millar, Jennifer L.; Schubert, Michael C. (Journal of otology, 2021)
The video head impulse test (vHIT) is used as a measure of compensation yet it’s stability in patients with vestibular pathology is unknown. 144 patients (n = 72 female, mean 54.46 ± 15.8 years) were grouped into one of three primary diagnoses (Peripheral, Central, or Mixed). Subjects were further categorized based on sex (male versus female), ear (left versus right; ipsilesional versus contralesional), age (six groups ranging from 19 to 84 years), and duration between visits (five groups, mean 191.46 ± SE 29.42 days, median 55.5 days). The gain of the VOR during passive head rotation was measured for each semicircular canal (horizontal, anterior, posterior). There was no difference in the VOR gain within any semicircular canal between the two visits (horizontal: p = 0.179; anterior: p = 0.628; posterior: p = 0.613). However, the VOR gain from the horizontal canals was higher than the vertical canals for each visit (p < 0.001). Patients diagnosed with peripheral vestibular pathology had significantly lower (p ≤ 0.001) horizontal semicircular canal gains at each visit. There was no difference in VOR gain between sex (p = 0.215) or age groupings (p = 0.331). Test-retest reliability of vHIT in patient subjects is good (ICC = 0.801) and the VOR gain values across two separate visits were significant and positively correlated (r = 0.67) regardless of sex, ear, age, or duration between visits. The vHIT is a stable measure of VOR gain over two different times across a variety of vestibular patients with no influence of age or sex.